Knowledge, Attitudes, and Social Responsiveness Toward Corona Virus Disease 2019 (COVID-19) Among Chinese Medical Students—Thoughts on Medical Education - Yang, Haojun; Zheng, Yue; Yu, Fang; Cheng, Bohao; Zhu, Ziqing; Liao, Sheng; Chen, Yu; Wu, Jianzhen; Wang, Fang (Frontiers in Medicine, 2021)
Purpose: To assess knowledge, attitudes and social responsiveness toward COVID-19 among Chinese medical students. Methods: Self-administered questionnaires were used to collect data from 889 medical students in 3 well-known Chinese medical universities. The questionnaire was comprised of three domains which consisted of demographic characteristic collection, 7 items for knowledge, 8 items for attitudes and social responsiveness toward COVID-19. Data from different universities were lumped together and were divided into different groups to compare the differences, including (1) students at clinical learning stage (Group A) or those at basic-medicine stage (Group B); (2) students who have graduated and worked (Group C) or those newly enrolled (Group D). Results: Medical students at group B had a weaker knowledge toward COVID-19 than did students at group A, especially in the question of clinical manifestations (p < 0.001). The percentage of totally correct answers of COVID-19 knowledge in group C was higher than that in Group D (p < 0.001). There were significant differences between group C and D in the attitudes and social responsiveness toward COVID-19. Surprisingly, we found the idea of new-enrolled medical students could be easily affected by interventions. Conclusions: In light of this information, medical education should pay attention not only to the cultivation of professional knowledge and clinical skills, but also to the positive interventions to better the comprehensive qualities including communicative abilities and empathy.